A single stent strategy in patients with lifestyle limiting claudication: 3‐year results from the Durability II trial. Issue 1 (25th February 2015) - Rocha‐Singh, Krishna J.; Bosiers, Marc; Schultz, Greg; Jaff, Michael R.; Mehta, Manish; Matsumura, Jon S.; for the Durability II Investigators
<x xml:space="preserve">Abstract</x> Objectives To evaluate longer‐term safety and efficacy of a single self‐expanding stent up to 20 cm in length in patients with atherosclerotic disease of the superficial femoral (SFA) and proximal popliteal arteries. Background Angioplasty and stenting are options for revascularization of symptomatic peripheral artery disease. While angioplasty alone is effective in short lesions, outcomes in longer lesions (i.e., mean 8.7 cm) show suboptimal patency rates of 33% at one year. Methods Two hundred eighty‐seven patients (mean age 68 years, 66% male) were treated with the EverFlex™ Self‐Expanding Peripheral Stent System. Patients were followed through 3 years with yearly core lab adjudicated duplex ultrasonography for patency, radiographic assessment of stent fractures, and resting ankle brachial indices. Results Overall freedom from loss of primary patency at 3 years was 60.0%. Patency was significantly higher for lesions ≤8 cm compared with lesions >8 cm (71.0 vs. 50.5%, P < 0.0001). There was no significant difference in patency between single‐stent and multistent recipients (60.4 vs. 52.4%, P = 0.343). The three‐year freedom from clinically driven target lesion revascularization was 70.0%. At 3 years, the overall stent fracture rate was 0.9%. Conclusions DURABILITY II is the first investigational device exemption trial to report 3‐year duplex Doppler defined stent patency and CD‐TLR outcomes in long SFA and proximal popliteal lesions and demonstrated acceptable stent patency and freedom from CD‐TLR with a low fracture rate. These data suggest that use of a single long stent provides reasonable long‐term outcomes when intervention is required for symptomatic SFA and proximal popliteal arterial disease. © 2015 Wiley Periodicals, Inc.